(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article provides information on the agrochemical properties of light gray soils of the Asaka district . Preliminary research data on the chemical composition and nutrients of these soils are presented. The biogeochemical properties of irrigated light gray soils are described.